ARE GOVERNMENT BANKS LESS COMPETITIVE THAN PRIVATE BANKS? EVIDENCE FROM INDONESIAN BANKING - Tri Mulyaningsih; Anne Daly; Phil Lewis; Riyana Miranti (Journal of Applied Economics in Developing Countries, 2014)
Literature suggests that compared to private banks, state-owned banks have lower incentives to maximize profit. This study aims to investigate the possible different competitive behaviour of state-owned banks and private banks. The recent refinement of Panzar-Rosse method by Bikker, Shaffer, and Spierdijk (2011) was employed to estimate the competitive behaviour of state-owned and private banks. The empirical estimation of Fixed-Effect approach shows that the H-statistics of the state-owned banks was significantly smaller than of the private banks. It implies that private banks behaved more competitively than the state-owned banks. The private bank market was close to perfect competition or monopolistic competition where bank products are regarded as perfect substitutes for one another. In contrast, state-owned banks attempted to collude rather than to compete to generate a maximum profit. State-owned banks behaved less competitive because they served the interest of government or politician, have a long hierarchical organisational design, receive an interest rate subsidies and an implicit guarantee from government against failure and their business are being controlled by government.Keywords: Bank ownership, competitive behaviour, Panzar-Rosse